2012
DOI: 10.1007/s00223-012-9642-1
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Calcification and Bone Metabolism: The Relationship between Aortic Calcification, BMD, Vertebral Fracture, 25-Hydroxyvitamin D, and Osteocalcin

Abstract: The aim of this study was to investigate the relationship between aortic calcification (AC) and low bone mineral density (BMD), 25(OH)D, C-terminal telopeptide (CTx), and osteocalcin levels in Asian women. We also tried to find the association between AC and the risk of vertebral fracture. We included 769 patients in this study. All patients underwent QCT. Aortic calcium score (ACS) was quantified by the Agatston scoring method. Spinal fracture was defined by lumbar spine radiography. Among 769 subjects, 96 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
6
30
2
1
Order By: Relevance
“…If anything, there was a suggested inverse association between plasma OC and aortic calcification in older-old women, with a higher degree of aortic calcification at lower plasma OC levels. This corresponds with the results of relatively large studies carried out in community-dwelling populations demonstrating inverse relationships between circulating OC and progression of atherosclerosis (17,38,39,40). The authors attribute this apparent protective effect of OC to a plausible indirect effect via its regulation of glucose and fat metabolism or other unidentified pathways.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…If anything, there was a suggested inverse association between plasma OC and aortic calcification in older-old women, with a higher degree of aortic calcification at lower plasma OC levels. This corresponds with the results of relatively large studies carried out in community-dwelling populations demonstrating inverse relationships between circulating OC and progression of atherosclerosis (17,38,39,40). The authors attribute this apparent protective effect of OC to a plausible indirect effect via its regulation of glucose and fat metabolism or other unidentified pathways.…”
Section: Discussionsupporting
confidence: 84%
“…Experimental studies have suggested that fat and glucose metabolism is regulated by the undercarboxylated isoform (7). Nevertheless, measures of carboxylated or total OC concentrations have been associated with CVD and metabolic risk factors in several studies (9,11,12,14,20,32,40), including LASA (16). The use of mid-date between interviews due to the lack of exact event dates for selfreported CVD is also a limitation with the potential to dilute the true associations.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 5400 men aged 65 years and older, severe AAC (>8 on the 24-point scale) was associated with a significantly higher risk of hip fracture, but not with the risk of other non-vertebral fractures (26). Several (11,20,(25)(26)(27), but not all (14) studies showed that severe AAC is associated with low BMD at various skeletal sites after adjustment for age. Mild AAC is not associated with lower BMD.…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 98%
“…Since then, several clinical studies on the association between osteocalcin and atherosclerosis and CVD have been reported. Some studies demonstrated that serum osteocalcin levels were inversely associated with atherosclerotic parameters and artery calcification [52][53][54][55][56][57][58][59] ; however, other studies reported otherwise 60,61) . Sheng et al 52) showed that serum osteocalcin levels were significantly and inversely associated with IMT and carotid plaques in men with T2DM via a multiple adjustment analysis.…”
Section: Effects Of Osteocalcin On Vascular Cells and Atherosclerosismentioning
confidence: 99%
“…Yang et al 53) conducted a further large-scale cross-sectional study and showed that serum osteocalcin levels were negatively associated with IMT in 1,319 Chinese postmenopausal women without any history of CVD or carotid plaque. Kim et al 54) reported that serum osteocalcin showed an age-independent association with aortic calcification scores. We also demonstrated that decreased serum osteocalcin and ucOC levels were significantly associated with increased aortic calcification scores in men with T2DM 55) .…”
Section: Effects Of Osteocalcin On Vascular Cells and Atherosclerosismentioning
confidence: 99%